An active technique for power saving in WSN under additive white gaussian noise channel - Raad Farhood Chisab (Institute of Advanced Engineering and Science, 2019)
The work with feature of self-power supply by solar cell or by the battery or together at the same time. Therefore, the power dissipation is the big problem in wireless sensor network (WSN) especially when it is works for long time. The efficient method for reducing the power consumption within working is needed. The process of reducing waste power is one of the top priorities of scientists and designers of wireless sensor networks. The aim of this paper is to find the dominant method to reduce the power consumption in the wireless sensor network in order to stay works for long time and maintain the links with other nodes without loss of connection and transfer the information correctly. In this paper, a modified method was invented to minimize power utilization per data bit in a connection. This new method depends on the optimization process for reducing the power consumption as low as possible. All the tests of simulation process were done in additive white Gaussian noise (AWGN) channel. Numerical results demonstrated that the new method reduce the power when different values of noise are present with different types of modulation. Also the distance that the WSN will reach the information to it will be increase with presence of various noise amounts with different types of modulation. As a result, the power was decreased and the signal was reach more distance.